Clarifying Heirs’ Rights in Indonesian Waqf Law: Toward Stronger Governance and Conflict Prevention - Al-Anshori, Huzaimah; Syamsudin, M.; Triyanta, Agus; Ramadhita, Ramadhita; Bachri, Syabbul; Alotaibi, Hajed A. (Nurani, 2025)
This research analyzes the current legal framework governing the rights of a wakif’s heirs under Indonesian waqf law and proposes a model of regulatory reform aimed at enhancing waqf governance and minimizing potential inheritance disputes. The urgency of this research arises from the increasing number of waqf dispute cases brought before Indonesian Religious Courts, many of which involve heirs claiming ownership of assets already pledged as waqf. These disputes reflect ongoing legal uncertainty and the lack of clear regulatory provisions governing heirs’ procedural rights, a condition that risks weakening both the long-term sustainability of waqf management and the overall stability of the legal system. The objectives of this study are twofold: (1) to analyze the normative and socio-legal factors contributing to heirs’ involvement in waqf disputes, and (2) to propose a legal reform framework that clarifies their position within the waqf system. Using a normative juridical method with statutory and conceptual approaches, the study finds that the ambiguity of Law No. 41 of 2004 concerning Waqf, particularly the absence of the term “wakif’s heirs” in Article 6, creates interpretive gaps leading to recurrent ownership claims. To address these issues, this paper proposes revising the Waqf Law to explicitly recognize the limited supervisory rights of heirs while maintaining the sanctity of waqf as perpetual charity. This proposed reform seeks to align the principles of Islamic jurisprudence with national law in order to ensure legal certainty, reduce the potential for disputes, and strengthen the overall effectiveness of waqf governance. The study contributes conceptually by redefining heirs’ legal standing and practically by promoting a conflict-resilient and sustainable waqf ecosystem in Indonesia.